System of independent work activities for learning oxidation-reduction reactions (REDEL. Revista Granmense de Desarrollo Local, 2021)
The research deals with the need to promote the independent learning of oxidation-reduction reactions in the teaching-learning process of the Chemistry subject in eleventh-grade students of the IPU “Micaela Riera” of Manzanillo. A system of independent work activities is presented and founded with various activities to be developed in the teaching-learning process of said subject, which have been developed taking into account the psycho-pedagogical characteristics of this type of student. The development is based on the use of theoretical methods, such as analytical-synthetic and inductive-deductive; methods of the empirical level, among them: the observation, the survey, the interview, and the pedagogical experiment, as well as the mathematical one of the statistical level. The current and novelty of the research lies in the dynamic nature of the different planned activities and at the same time its developer nature, which contribute to the learning of the Chemistry subject in an active and conscious way.